Oportunidades Divergentes de Innovación: Cuando tanto el momento como la situación importan (Revista Galega de Economía)
This paper investigates the rich diversities of innovation which are characterised not only by location or country and regional context of an enterprise but also by a wider context which can even be defined globally. The research argues that these diversities of innovation demand appropriate strategies and a concertation of capabilities in given situations. The paper shows how the opportunities emerge from technologies, organisation of manufacturing and research and how they are associated with constant changes of skills, products and demand. Moreover, the process describes how processes of innovation have become highly collaborative in R&D and also with regard to the supply of high-quality parts to international chains of innovation. These situations have also become important opportunities to contribute and participate based on specialised competences to take advantage of highly diverse processes of innovation and embeddedness in global division of labour. Finallty, synergy with traditional competences may help to exploit opportunities in an unique way that create sustainable differentiation.